Lupus anticoagulant testing during anticoagulation, including direct oral anticoagulants - Favaloro, Emmanuel J.; Pasalic, Leonardo (Research and practice in thrombosis and haemostasis, 2022)
Lupus anticoagulants (LA) are one laboratory criterion for classification of antiphospholipid syndrome, with presence of vascular thrombosis and/or pregnancy/fetal morbidity being clinical criteria. The presence of LA is detected (or excluded) by laboratory testing, with the activated partial thromboplastin time and dilute Russell's viper venom time the most commonly used tests. Given the association of thrombosis with LA, it is no surprise that anticoagulants are used to treat or manage such patients. To review and discuss interferences from anticoagulants on LA testing, and strategies to mitigate these. This narrative review assessed interference from commonly used anticoagulants, focusing on LA testing while on direct oral anticoagulants (DOACs), including use of DOAC neutralizers. The classical anticoagulants comprise vitamin K antagonists such as warfarin, and heparins, predominantly unfractionated heparin and low molecular weight heparin (LMWH). DOACs have emerged with favorable efficacy and safety. These comprise two classes: direct anti‐thrombin (anti‐IIa; dabigatran) or direct anti‐Xa (rivaroxaban, apixaban, edoxaban) agents. All anticoagulants affect clotting assays, although there are differences in effects according to anticoagulant and assay. Nevertheless, because of such interferences, anticoagulants can lead to false‐negative or false‐positive LA findings. Several strategies can mitigate such interferences, including avoidance of testing while patients are on such anticoagulants, temporarily switching to an anticoagulant (i.e., LMWH) with less assay interference, testing for LA at nadir levels of anticoagulants, and/or use of anticoagulant neutralizers. Whilst the best approach is to avoid LA testing on patients taking anticoagulants; if unavoidable, testing may be facilitated by various mitigating strategies.